2021
DOI: 10.7759/cureus.17741
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Involvement in Oesophageal Carcinoma: A Single-Centre Observational Study From Western India

Abstract: IntroductionLymph node involvement is the most important predictor of prognosis in oesophageal cancer. The present study describes our single-centre experience of lymphadenopathy in oesophageal carcinoma cases at a tertiary care centre in the Marathwada region of Maharashtra state in western India. MethodsThis descriptive study included 31 patients who were operated for oesophageal carcinoma at the State Cancer Hospital in Marathwada from August 2015 to September 2017. Thirty patients underwent three-field lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, adenocarcinoma is the predominant histological subtype in Europe and United States. 3,4 Multimodality neoadjuvant therapy for oesophageal cancer is increasingly applied worldwide, since it has shown a survival benefit over surgery alone. 5 Neoadjuvant chemoradiation therapy for oesophageal adenocarcinoma has been widely used to treat patients with locally advanced and/or lymph node positive tumours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adenocarcinoma is the predominant histological subtype in Europe and United States. 3,4 Multimodality neoadjuvant therapy for oesophageal cancer is increasingly applied worldwide, since it has shown a survival benefit over surgery alone. 5 Neoadjuvant chemoradiation therapy for oesophageal adenocarcinoma has been widely used to treat patients with locally advanced and/or lymph node positive tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Oesophageal squamous cell carcinoma is the predominant histological type worldwide. However, adenocarcinoma is the predominant histological subtype in Europe and United States 3,4 . Multimodality neoadjuvant therapy for oesophageal cancer is increasingly applied worldwide, since it has shown a survival benefit over surgery alone 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The LNM rate of ESCC was 42.2–51.2% 5 , 14 , 17 , 29 according to previous studies. We proposed a model with excellent interpretability based on a beta‐binomial distribution.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have indicated that T stage, histopathology, differentiation grade, tumor size, and neoadjuvant therapy are the main factors affecting LNM in EC. 7 , 14 , 15 , 16 , 17 , 18 T stage was the most crucial factor for LNM in ESCC 19 : the deeper the tumor invasion, the easier it is for the tumor cells to enter the lymphatic vessels. Consequently, LNM rates have significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…On this standard, we reviewed the distribution of examined LNs count (the median was 20) and inferred more than 50% of patients from our data had received a limited lymphadenectomy. The nodal disease rate of ESCC was 42.2-51.2% in previous researches [11,[17][18][19] . Our apparent prevalence of the nodal disease is 53.7%, and the corrected prevalence is 61.2% after accounting for missing potential positive cases.…”
Section: Discussionmentioning
confidence: 83%